Identification of The Potential of Batang Kenaikan Rafting as A Contextual Physics Learning Resource Through Needs Analysis of Senior High School Students - Yusella, Nur Ummi (Universitas Negeri Padang, 2025)
Arung Jeram Batang Kenaikan is one of the natural attractions that holds great potential to be utilized as a contextual physics learning resource. This tourist attraction is often visited by young people, especially high school students. However, the attraction is only utilized as a place of entertainment, such as taking pictures and playing. They do not realize that the tourist attraction they visit can be used as a learning resource, especially in understanding physics concepts. This research aims to identify the potential of Batang Kenaikan Rafting as a contextual physics learning resource by analyzing students' needs for physics teaching materials in high school. The research method used is preliminary research and development with the Edupark approach which is focused on three initial stages, namely edupark finding (E), Direct Observation (D), and Understanding of Analysis Students, Teachers, Curriculum Characteristics (U). Data were collected through direct observation, questionnaires of students' needs, and interviews with physics teachers. The observation results show that the tourist attraction of Arung Jeram Batang Kenaikan contains various physics concepts such as Newton's law, fluid, kinematics, and energy. The needs analysis shows that the majority of students have a visual learning style and are interested in physics learning based on the real environment. Based on these findings, it can be concluded that Arung Jeram Batang Kenaikan has high potential to be developed as a physics Edupark that is contextual and in accordance with the characteristics of students, and supports the effective implementation of the Merdeka Curriculum.